The Prevalence and Determinants of Hand and Face Dermatitis during COVID-19 Pandemic: A Population-Based Survey - Mohammed Saud Alsaidan; Aisha H. Abuyassin; Zahra H. Alsaeed; Saqer H. Alshmmari; Tariq F. Bindaaj; Alwa’ad A. Alhababi (Dermatology Research and Practice)
Background. During the current COVID-19 pandemic, prevention is the key to limiting the spread of this disease. The frequent handwashing and use of sanitizers resulted in notable skin changes among some individuals. The aim of the study was to determine the prevalence and determinants of the new onset of dermatitis during the COVID-19 pandemic in a university population from Saudi Arabia. Methods. A cross-sectional study was conducted using a self-administered online questionnaire by sending an invitation link to students and employees of Prince Sattam Bin Abdulaziz University in June 2020. A chi-squared test was used to note differences regarding hand and face dermatitis. Results. Of the total 2356 participants, 34.8% reported skin changes or symptoms over hands, and 15.3% reported skin changes on their face during this pandemic. 88.7% of the participants reported a change in handwashing habits during the COVID-19 pandemic, and 62.2% of participants were not using any hand sanitizers before COVID-19 but began using them during the pandemic. There were significantly higher percentage of skin conditions in females (on hands (ScH): 42.6% and face (ScF):19.2%), individuals working in environments requiring frequent handwashing (ScH: 40.3% vs. ScF: 17.2%), those working in facilities where they have to interact with people during the pandemic (ScH: 41.1% vs. ScF: 18.7%), those encountering COVID-19 patients (ScH: 48.6% vs. ScF: 24.8%), those exposed to chemicals (ScH: 48.6% vs. ScF: 24.8%), and healthcare workers (ScH: 51.3% vs. ScF: 24.3%). Conclusion. It was found that during the pandemic, skin changes were common among the general population as well as among healthcare workers. The frequency of handwashing and the use of alcohol-based sanitizers were contributing factors for dermatitis. Although hygiene is an extremely important preventive measure in this pandemic, maintaining skin integrity is also vital. Appropriate knowledge and good practice can prevent dermatitis in this pandemic, with regular hydration of the skin being a key factor.